Valuation of coral reefs using site choice model - Katsuhito Nohara; Azusa Okagawa; Akira Hibiki; Hiroya Yamano (European Regional Science Association (ERSA), 2016)
The coral reef ecosystems provide many goods and services to coastal populations, such as tourism. Furthermore, they form a unique natural ecosystem, with an important biodiversity value as well as scientific and educational value. They also form a natural protection against wave erosion. However, they have been damaged due to red soil erosion and global warming. Therefore, the preservation of coral reefs has been an important policy issue. The cost benefit analysis of the policy is important to choose cost-effective policy. A few studies have evaluated the economic value of coral reefs in Okinawa prefecture, Japan, but most of them have applied contingent valuation method. The purpose of this study is to estimate the value of coral reefs which tourists to Okinawa prefecture obtain using discrete choice travel cost method. We implemented an on-site survey to tourists to Okinawa at Naha airport, Ishigaki airport, Miyako airport and Kumejima airport on November 8th to 11th in 2013 and collected 410 responses. A total of 163 responses were excluded from data analysis because they were not fully completed. We applied conditional logit model to tourist's decision to select his/her destination and estimate the model using collected data. Based on the conditional logit model, the hypothesis of Independence from Irrelevant Alternatives (IIA) cannot be rejected. We also tried to apply mixed logit model to our data but there was no significant difference between random parameters and not random ones. The main findings are willingness to pay by a tourist for coral reefs is 4,754 yen/km2 per a day and16,544 yen/km2 per trip.
Keywords: 330; the value of coral reefs; discrete choice travel cost method; marginal willingness to pay